Tadpoles in lotic waters, habitat specialization, and human population density lead tree frogs (Hylinae) to higher extinction risk - Luría-Manzano, Ricardo; Serrano, Filipe C.; Böhm, Monika; Sawaya, Ricardo J.; Haddad, Célio F.B. [UNESP]; Martins, Marcio (Elsevier, 2024)
Analyzing patterns of vulnerability to extinction across clades and traits that make species more prone to extinction are crucial steps towards prioritization of conservation efforts. Here we identified genera more vulnerable to extinction than expected by chance within the anuran subfamily Hylinae. We also investigated a broad range of intrinsic and extrinsic factors and their interactions as predictors of a proxy for extinction risk (IUCN Red List status). By conducting simulation analyses, we found that binary threat status is not randomly distributed across Hylinae genera, with Charadrahyla, Hyloscirtus, Isthmohyla, Plectrohyla, and Sarcohyla containing more threatened species than expected by chance. By using model selection and average approaches, we found strong support for increased likelihood of threatened status as habitat diversity decreases and human population density increases, and for species with larvae inhabiting lotic waters to be more threatened than those with larvae inhabiting lentic waters. Overall, our results were robust to different treatments of Data Deficient species (threatened or non-threatened). However, results were affected by the inclusion of geographic range size as another predictor, with habitat diversity becoming a non-significant predictor of threatened status. Our results highlight the importance of simultaneously analyzing both intrinsic and extrinsic predictors in correlative studies of extinction risk. Additionally, they underscore the need for conservation research and programs focused on both larvae and adults of organisms with biphasic life cycles and the establishment and evaluation of effectiveness of natural refuges far from areas under high human pressures, such as privately and community protected areas.
Keywords: Conservation status; IUCN Red List; Larval habitat; Neotropical region; Population trend; Vulnerability to extinction